2013
DOI: 10.1371/journal.pone.0061026
|View full text |Cite
|
Sign up to set email alerts
|

Drug Screening for Autophagy Inhibitors Based on the Dissociation of Beclin1-Bcl2 Complex Using BiFC Technique and Mechanism of Eugenol on Anti-Influenza A Virus Activity

Abstract: Autophagy is involved in many human diseases, such as cancer, cardiovascular disease and virus infection, including human immunodeficiency virus (HIV), hepatitis C virus (HCV), influenza A virus (IAV) and coxsackievirus B3/B4 (CVB3/B4), so a drug screening model targeting autophagy may be very useful for the therapy of these diseases. In our study, we established a drug screening model based on the inhibition of the dissociation of Beclin1-Bcl2 heterodimer, an important negative regulator of autophagy, using b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(84 citation statements)
references
References 45 publications
(73 reference statements)
1
77
0
1
Order By: Relevance
“…Eugenol also ameliorated the oxidative stress and inhibited the expressions of autophagic genes. Beclin1-Bcl2 heterodimer, autophagy, and impaired IAV replication suggested that eugenol is the promising inhibitor for autophagy and IAV infection [49].…”
Section: Antiviral Activitymentioning
confidence: 99%
“…Eugenol also ameliorated the oxidative stress and inhibited the expressions of autophagic genes. Beclin1-Bcl2 heterodimer, autophagy, and impaired IAV replication suggested that eugenol is the promising inhibitor for autophagy and IAV infection [49].…”
Section: Antiviral Activitymentioning
confidence: 99%
“…As a functional ingredient, it is included in many dental preparations and it has also been shown to enhance skin permeation of various drugs. 4) In recent years, eugenol has been reported to have antioxidant, 5) anti-inflammatory, 6) anti-viral 7) and anticancer [8][9][10] activities. Although beneficial effects of eugenol on oxidative stress and inflammation have been well-studied, pharmacological effects on metabolic diseases are largely unknown.…”
mentioning
confidence: 99%
“…In the process of inflammation, lung itself has antioxidant defense system. Under normal conditions, the body possesses a set of free radical scavenging enzymes (superoxide dismutase SOD and glutathione peroxidase GSH-PX), which keeps a equilibrium state at low concentration (Dai et al, 2013); when Table 2 Effects of HXD and ribavirin on H1N1 influenza infected mice.…”
Section: Effects Of Hxd On Cytokines and Anti-oxidant Factor In Serummentioning
confidence: 99%